2016
DOI: 10.1002/chem.201503753
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of Peptides by Silver‐Promoted Coupling of Carboxylates and Thioamides: Mechanistic Insight from Computational Studies

Abstract: The mechanism of the recently described N→C direction peptide synthesis through silver-promoted coupling of N-protected amino acids with thioacetylated amino esters was explored by using density functional theory. Calculation of the potential energy surfaces for various pathways revealed that the reaction proceeds through silver-assisted addition of the carboxylate to the thioamide, which is followed by deprotonation and silver-mediated extrusion of sulfur as Ag2 S. The resulting isoimide is the key intermedia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
12
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
3
2

Relationship

3
2

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 38 publications
0
12
0
Order By: Relevance
“…[24] We propose that the same process in an intramolecular reaction results in aAg I -templated cyclization (Figure 4), reminiscent of the metal-ion-templated cyclization reactions of peptide thioesters. [24] We propose that the same process in an intramolecular reaction results in aAg I -templated cyclization (Figure 4), reminiscent of the metal-ion-templated cyclization reactions of peptide thioesters.…”
Section: Angewandte Chemiementioning
confidence: 92%
See 3 more Smart Citations
“…[24] We propose that the same process in an intramolecular reaction results in aAg I -templated cyclization (Figure 4), reminiscent of the metal-ion-templated cyclization reactions of peptide thioesters. [24] We propose that the same process in an intramolecular reaction results in aAg I -templated cyclization (Figure 4), reminiscent of the metal-ion-templated cyclization reactions of peptide thioesters.…”
Section: Angewandte Chemiementioning
confidence: 92%
“…Our previous mechanistic studies of the intermolecular reaction showed that Ag I coordinates to both the carboxylate and the thioamide. [24] We propose that the same process in an intramolecular reaction results in aAg I -templated cyclization (Figure 4), reminiscent of the metal-ion-templated cyclization reactions of peptide thioesters. [10] Importantly,inthis process the Ag I both chemoselectively activates the thioamide to nucleophilic attack by the carboxylate,a nd templates the cyclization by bringing the N-a nd C-termini in close proximity,t hereby overcoming the entropic barrier to cyclization resulting in af ast reaction.…”
Section: Angewandte Chemiementioning
confidence: 99%
See 2 more Smart Citations
“…Our group has recently developed a new method for peptide synthesis through the Ag I ‐promoted reaction of thioamides with peptide C ‐terminal carboxylic acids, which has been exploited in the epimerization‐free synthesis of peptides in the N→C direction (Scheme b) . This thioamide‐directed peptide synthesis proceeds through the generation of an isoimide intermediate, which can rearrange to an imide via an O→N acyl transfer (Scheme a).…”
Section: Methodsmentioning
confidence: 99%